Associação entre estresse oxidativo, inflamção e manifestações sistêmicas e tabagistas pacientes com DPOC leve e moderada - Caram, Laura Miranda de Oliveira [UNESP] (2015)
The aim of this study was to evaluate the association between oxidative stress and inflammatory markers and their relationship with muscle strength, systemic muscle mass, exercise capacity, quality of life in smokers, mild/moderate COPD patients and nonsmokers controls. Were evaluated 32 active smokers (smoking history> 10 pack/years) without COPD, 32 mild/moderate COPD patients [current smokers or former smokers (smoking history> 10 pack/years) and 32 nonsmokers. All individuals underwent to medical and smoking status evaluations, spirometry pre and post-bronchodilator and pulse oximetry. The concentration of inflammatory mediators [C-reactive protein (CRP), interleukin (IL) 6, and tumor necrosis factor-alpha receptors (TNFR1 and TNFR2)] and indicators of oxidative stress [advanced glycation end-products (AGEs) and soluble receptors for advanced glycation end-products (sRAGE)] were measured in serum. We assessed body composition by bioimpedance, peripheral muscle strength by dynamometry, exercise capacity (six minutes walk distance) and the health status through the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) and the Hospital Anxiety and Depression Scale (HAD). Smokers (p<0.001) and COPD patients (p<0.001) had higher values of AGEs when compared to controls there was no statistically significant difference between smokers and COPD patients. The sRAGE concentrations did not differ between groups (p=0.92). Smokers (p=0.01) and patients with COPD (p=0.01) showed higher values of CRP compared to controls, there was no statistical significant difference between smokers and COPD groups. The concentrations of IL-6 (p=0.07) and TNFR1 (p=0.07) did not differ between groups. Regarding concentrations of TNFR2, COPD patients showed higher values when compared to smokers (p=0.004) and controls (p=0.004). We identified positive association of smoking (p=0.04), CRP (p=0.03) and IL6 (p=0.03) with the concentrations of AGEs. The ...